Case report: Consecutive hyperbaric oxygen therapy for delayed post-hypoxic leukoencephalopathy resulting from CHANTER syndrome caused by opioid intoxication - Jingami, Naoto; Cho, Kosai; Nitta, Takayuki; Takatani, Miwa; Kobayashi, Katsuya; Takenaka, Ryo; Sugita, Naoko; Ohtsuru, Shigeru (Frontiers in Medicine, 2024)
Delayed post-hypoxic leukoencephalopathy (DPHL) is a poorly recognized syndrome characterized by neuropsychiatric symptoms following recovery from an acute hypoxic episode. Although most cases are related to carbon monoxide poisoning, some have been linked to excessive opioid use.Opioid intoxication has recently become known for manifesting the characteristic imaging findings involving cerebellar, hippocampal, and basal nuclei transient edema with restricted diffusion (CHANTER) syndrome. Herein, we present a patient with severe disturbances in consciousness who was initially diagnosed with CO poisoning but was later found to have taken excessive tramadol.Magnetic resonance imaging (MRI) in the acute phase revealed abnormal intensities in the bilateral globus pallidus and the cerebellum, indicative of CHANTER syndrome. After intensive care, his level of consciousness was restored. However, around the 3rd week after hospitalization, his consciousness gradually deteriorated and he developed severe neurological symptoms. Another MRI on day 25 revealed a new diffuse white matter abnormality; DPHL was suspected. Cerebrospinal fluid collected on day 28 revealed significantly elevated myelin basic protein levels. Although it was challenging to decide on a treatment plan, hyperbaric oxygen (HBO) therapy trials were initiated on day 58; the patient's condition improved after a series of HBO sessions. MRI revealed gradual shrinkage of the white matter abnormality. A total of 63 consecutive HBO sessions were performed, leading to the successful resolution of the serious neurological symptoms. While the effectiveness of HBO therapy for DPHL remains inconclusive, especially in opioid-related cases, this patient made a remarkable recovery, likely due to the therapeutic effect of improved cerebral blood flow and oxygenation.